Kepribadian Tokoh Sato Reang pada Novel Anjing Mengeong, Kucing Menggonggong Karya Eka Kurniawan: Psikoanalisis Carl Gustav Jung - Pratama, Rangga Kari; Hadi, Wisman; Ritonga, Mara Untung; Chairunisa, Hera (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to reveal the factors that influence the formation of the character Sato Reang’s personality and to analyze the structure and dynamics of his personality based on Carl Gustav Jung’s psychoanalytic theory. This research employs a descriptive qualitative method using a literary psychology approach. The data source is the novel Anjing Mengeong Kucing Menggonggong by Eka Kurniawan. Data collection techniques include intensive reading, note-taking, and interpretation using Jungian psychoanalysis as the analytical tool. The findings show that Sato Reang’s personality formation is influenced by repressive social and religious experiences since childhood, particularly his relationships with authoritarian figures and the imposition of religious values. These experiences give rise to inner conflicts and shape a resistant personality that is deeply involved in a search for meaning. Psychologically, Sato’s ego develops reflectively with a dominant introverted attitude and the functions of feeling and intuition. His personal unconscious is dominated by paternal and religious complexes, while his collective unconscious reveals a rebellious persona, a destructive shadow, and an incomplete journey toward the self. His personality dynamics reflect the principles of equivalence, entropy, progression, and regression, indicating psychic tension resulting from the conflict between inner needs and social pressures. Thus, the character of Sato Reang represents an individual who fails to complete the individuation process due to persistent trauma and repression within his psychic structure.Keywords: Jungian psychoanalysis, consciousness, unconsciousness, personality dynamics, Sato Reang.